A theoretical model of the evolution of virulence in sexually transmitted HIV/AIDS - FAB Coutinho; E Massad; RX Menezes; MN Burattini (Universidade de São Paulo, 1999)
INTRODUCTION: The evolution of virulence in host-parasite relationships has been the subject of several publications. In the case of HIV virulence, some authors suggest that the evolution of HIV virulence correlates with the rate of acquisition of new sexual partners. In contrast some other authors argue that the level of HIV virulence is independent of the sexual activity of the host population. METHODS: Provide a mathematical model for the study of the potential influence of human sexual behaviour on the evolution of virulence of HIV is provided. RESULTS: The results indicated that, when the probability of acquisition of infection is a function both of the sexual activity and of the virulence level of HIV strains, the evolution of HIV virulence correlates positively with the rate of acquisition of new sexual partners. CONCLUSION: It is concluded that in the case of a host population with a low (high) rate of exchange of sexual partners the evolution of HIV virulence is such that the less (more) virulent strain prevails.